The Effect of Financial Performance and Board of Independent on Tax Avoidance - Riaty Handayani (Jurnal Riset Akuntansi Terpadu, 2022)
Tax avoidance is not an illegal activity, reduced state revenues can hinder the country's economic growth, especially fiscal policy. This study aims to examine the effect of  financial performance and independent dean commissioners on tax avoidance. This study uses quantitative methods with cross-sectional data  and secondary data  obtained from the   financial statements of mining sector companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2021. The results showed that ROA and DER had a significant negative  effect  on tax avoidance.  Meanwhile, the independent board of commissioners has no effect on tax avoidance.